Conducting Health Disparities Research with Criminal Justice Populations: Examining Research, Ethics, and Participation - Valera, Pamela (2014)
This study explored the challenges of informed consent and understanding of the research process among Black and Latino men under community supervision (e.g., parole and/or probation). Between February and October 2012, we conducted cognitive face-to-face interviews using open-ended questions on the significant areas of research participation (i.e., the informed consent process, confidentiality, compensation, what is meant by human subject and clinical trials) among 259 men aged 35 to 67 under community supervision in Bronx, New York. Content analysis of the open-ended questions revealed limited knowledge concerning the understanding of research participation. The study participants appeared to generally understand concepts such as compensation after research participation and confidentiality. Participants demonstrated a lack of understanding of certain aspects of the research process—informed consent, human subject, Institutional Review Board, and clinical trials. These findings are informative to researchers conducting studies with criminal justice populations and Institutional Review Boards reviewing research studies.